Attitudes Toward Refugees Between Group-Focused Enmity and Other-Oriented Responsiveness: Evidence From Nationally Representative German Samples 2015/2016 and 2022 - Heinz Streib; Zhuo Job Chen (Journal of Social and Political Psychology)
What are the differences in attitudes toward incoming people who seek refuge from war and toward those who supposedly are coming because of the better living conditions? How could this attitudinal difference be explained? This article presents spotlights on the attitudes toward refugees in Germany based on national representative surveys in two periods, when the German borders were crossed (a) by high numbers of people fleeing the war in Syria in 2015 and early 2016 (n = 1,262), and (b) when in 2022 most refugees came from Ukraine (n = 1,339). Results based on a repeated cross-sectional design indicate that, during both periods of peak war-related refugee immigration, there was high agreement to accepting war refugees into Germany, which even increased between 2016 (81.1%) and 2022 (89.8%), while, in contrast, the majority (2016: 70.0%; 2022: 60.8%) resisted accepting refugees who supposedly seek only better living conditions. Further, using a newly designed model, we demonstrate that the Group-focused Enmity syndrome is negatively associated with the agreement to accept war refugees into Germany (β = -.31), but much more negatively with accepting supposedly ‘economic’ refugees (β = -.49), while the component of Other-oriented Responsiveness is positively associated with accepting war refugees (β = .23). The results document continuously high agreement to accepting war refugees into Germany; further the study opens a perspective on prejudice reduction and suggests understanding the attitudes to refugees in a model that tests the opposition between othering and responsiveness. Both key results invite further investigation.